PENGARUH PENGENDALIAN KOMUTASI HALL SENSOR TERHADAP KECEPATAN MOTOR BLDC - Batara Helda Firdauzy; Waru Djuriatno; Muhammad Aswin (Jurnal Mahasiswa TEUB, 2023)
A brushless DC motor, also known as a brushless DC motor (BLDC motor), is a type of synchronous motor. The BLDC motor used has advantages over ordinary DC motors, including not causing a brush, higher efficiency, almost no sound, long life, and other advantages. The purpose of this study was to determine the speed of the BLDC motor in steady state when the hall sensor wasdelayed and the torque load changed and to determine the settling time of the BLDC motor speed when the hall sensor was delayed and the torque load was changed. This control uses a delay that is installed on the hall sensor before entering the controller. This system is made with the simulation method on the PSIM application. Tests carried out using delay changes at values of 0 seconds, 0.002 seconds, 0.004 seconds, 0.006 seconds, 0.008 seconds and 0.01 seconds. Tests were also carried outusing changes in torque load on BLDC motors with values of 1 Nm, 2 Nm, 4 Nm, and 8 Nm. Based on the results of testing the change in delay and torque load on the BLDC motor, the delay value at the hall sensor commutation and the torque load value is inversely proportional to the BLDC motor speed and the settling time at BLDC motor speed is directly proportional to the torque load value on the BLDC motor and inversely proportional to the delay on hall sensor commutation in delay conditions 0.008 seconds and 0.01 seconds. Keywords-- BLDC Motor, hall sensor commutation control, delay, settling time. DAFTAR PUSTAKA[1] Kandiban, R., & Arulmozhiyal, R. (2012). Speed control of BLDC motor using adaptive fuzzy PID controller. In Procedia Engineering (Vol. 38, pp. 306–313). Elsevier Ltd. https://doi.org/10.1016/j.proeng.2012.06.039[2] Anugrah, R. F. (2020). Kontrol Kecepatan Motor Brushless DC Menggunakan Six Step Comutation Dengan Kontrol PID (Propotional Integral Derivative ). Jurnal Teknik Elektro Dan Komputer TRIAC, 7(2), 57–63.[3] Zhao, J., & Yangwei, Y. (2011). Brushless DC Motor Fundamentals Application Note. MPS, The Future of Analog IC Technology, (July 2011), 7–8.[4] Asuri, S. K. (2021). Modelling and Control of Sparse Converter Fed Induction Motor Drives, 58–80. Retrieved from https://www.tntech.edu/files/cesr/StudThesis/asuri/Chapter4.pdf[5] Wicaksono, A. S. (2016). Perancangan dan Implementasi Sistem Pengaturan Kecepatan Motor BLDC Menggunakan Kontroler PI Berbasiskan Neural-Fuzzy Hibrida Adaptif. Jurnal Teknik ITS, 5(2), 68–74. https://doi.org/10.12962/j23373539.v5i2.16272[6] Qudsi, O. A., Prasetyono, E., Ferdiansyah, I., Nugraha, S. D., & Purwanto, E. (2020). Soft Starting dengan Redaman Arus Starting Pada Motor BLDC, 2(September), 11.[7] Akbar, D., & Riyadi, S. (2019). Pengaturan Kecepatan Pada Motor Brushless Dc (Bldc) Menggunakan Pwm (Pulse Width Modulation), 255–262. https://doi.org/10.5614/sniko.2018.30[8] Kosanke, R. M. (2019). Performansi Sistem Pengendali Kecepatan Motor BLDC Menggunakan Logika Fuzzy Logic[9] Irawan, D., & Perdana SS, P. (2020). Kontrol Motor Brushless DC (BLDC) Berbasis Algoritma AI - PID. Jurnal Teknik Elektro Dan Komputasi (ELKOM), 2(1), 41–48. https://doi.org/10.32528/elkom.v2i1.3146 [10]Atmel. (2014). AVR1607 : Brushless DC Motor ( BLDC ) Control in Sensor, 1–18.[11]Yedamale, P. (2003). Brushless DC (BLDC) Motor Fundamentals, 1–20.[12]Brown, W. (2011). AN857 Brushless DC Motor Control Made Easy App. Note. Technology, 1–48.[13]Current, B. D., Motor, B., Software, C., & Xmc, I. (n.d.). BLDC motor control software using XMC. Retrieved from www.infineon.com